Unveiling resistance expression profile to powdery mildew in wheat via Bulked Segregant RNA-Seq - Tianying Yu; Shengliang Cao; Yuli Jin; Chunxia Xu; Ruobing Liu; Bo Wang; Yue Lv; Ting Meng; Pengtao Ma (BMC Plant Biology, 2024)
Abstract Background Developing wheat cultivars with durable resistance to powdery mildew, caused by Blumeria graminis f. sp. tritici (Bgt), is crucial for sustainable agriculture. The wheat genotype MYC exhibited high resistance to the Bgt isolate E09 at the seedling stage. Genetic analysis identified a recessive gene, temporarily named PmMYC, responsible for this resistance. Understanding the molecular mechanisms underlying this resistance is essential for advancing breeding programs. Results Bulked Segregant RNA-Seq revealed numerous alternative splicing events generated following Bgt infection, suggesting powdery mildew may disrupt alternative splicing and affect immune responses. Gene Ontology (GO) analysis indicated significant enrichment of differentially expressed genes in “response to stimuli” and “immune system processes”, implying their roles in disease defense. BSR-Seq analysis identified two high-confidence candidate regions for PmMYC on chromosome 2B, spanning 40,451,950 − 102,426,703 bp and 421,707,046–449,840,516 bp. Within these intervals, 740 genes were identified, with nonsynonymous mutations in 46 genes in the parents and bulks. Real-time PCR showed distinct expression profiles in four genes in resistant MYC compared to susceptible Yannong 21. KEGG and COG analyses of differentially expressed genes in candidate intervals revealed enrichment in immune processes related to plant-pathogen interactions, confirming that PmMYC initiated a broad immune response to prevent Bgt invasion. Conclusion The study identified key genetic intervals and genes involved in the resistance of wheat genotype MYC to Bgt. The identified genes, particularly those with altered expression profiles, could serve as valuable targets for breeding programs aimed at developing wheat cultivars with durable resistance to powdery mildew. These findings enhanced our understanding of plant-pathogen interactions and provided a foundation for future genetic and functional studies.